HLA-DRB1 allele distribution among children with rheumatic heart disease in Haji Adam Malik Hospital Medan, Indonesia - Tina Christina Lumban Tobing; Teddy Ontoseno; Sri Endah Rahayuningsih; Ratna Akbari Ganie; Yahwardiah Siregar (Medicinski glasnik, 2019)
Rheumatic heart disease (RHD) is influenced by genetic factor, microorganism's virulence, and environmental factor. The aim of this study was to determine human leukocyte (HLA)-DRB1 allele among children with RHD in Medan, Indonesia. Methods: An observational study was conducted at the Department of Child Health, Haji Adam Malik Hospital Medan from April to June 2017. Inclusion criteria were children aged 5-18 years diagnosed with RHD. Children with concomitant congenital heart disease were excluded. HLA-DRB1 alleles were analyzed using the PCR sequence-specific priming (SSP) technique. Statistical analysis was done using computer software. Results: A total of 62 children were enrolled. The mean age of children was 12.6 (SD 3.44) years; 33 (53.2%) were male. The most dominant allele was HLA-DRB1*12, followed by HLA-DRB1*15. Conclusion: It is proven in this research that RHD is influenced by genetic factor with HLA-DRB1*12 allele found to be the most common allele in children with RHD in Medan, Indonesia.
Keywords: cardiology; human leukocyte antigen; paediatric; RHD